Adipose Infiltration of the Dermis, Involving the Arrector Pili Muscle, and Dermal Displacement of Eccrine Sweat Coils: New Histologic Observations in Frontal Fibrosing Alopecia. (July 2019) - Miteva, Mariya; Castillo, David; Sabiq, Samar
Abstract : Background: Frontal fibrosing alopecia (FFA) is an irreversible scarring alopecia, and its incidence has reached epidemic size. Immune privilege collapse of the bulge and epithelial mesenchymal transition play a role in the pathogenesis. We have noted adipose tissue in the dermis in several specimens from FFA. Objective: Our primary objective was to verify the presence of adipose tissue at the isthmus level in biopsies from FFA. Additional objectives included the presence of deep inflammation and position of the sweat coils. Methods: Eighty-three histologic specimens of FFA diagnosed at the Dermatopathology Laboratory at the Department of Dermatology, University of Miami, within 3 years were evaluated retrospectively. All biopsies were bisected horizontally and assessed at several levels. Sixty biopsies from androgenetic alopecia served as controls. Statistical analysis was performed using the χ 2 test. A P value of 0.05 or less was considered significant. Results: Sixty specimens met the inclusion criteria for optimal quality and classic diagnostic features. Seventy percent demonstrated fat tissue infiltration at the isthmus level as clusters of cells or small globules versus 23% of the controls. The fat infiltration in the arrector pili muscle (APM) was present in 55% versus 15% of the controls, and the sweat coils were positioned in the reticular dermis in 43% versus 1.7% of the controls. All results were statistically significant ( P < 0.0001). When accounting for the simultaneous presence of any of these 3 variables, 30% of the FFA cases had triple positivity, 61.7% had double positivity, and 75% had at least 1 positive variable versus 0%, 15%, and 10%, respectively, of the controls. Conclusion: New histologic findings in FFA involve the presence of adipose tissue in the dermis. We believe that the close interaction of the hair follicles and the APM with the adipose tissue may play a role in APM degeneration and in epithelial mesenchymal transition.